Case Report: Treatment policy for female adolescents in the grip of chronic suicidality - Van de Koppel, M.; Mérelle, S. Y. M.; Stikkelbroek, Y. A. J.; Van der Heijden, P. T.; Spijker, J.; Popma, A.; Creemers, D. H. M. (Frontiers in Child and Adolescent Psychiatry, 2024)
INTRODUCTION: Within the Dutch clinical field of specialized mental health care for youth, an increasing subgroup of female adolescents with severe chronic suicidal behavior is recognized. This group was also identified in a Dutch psychological autopsy study among 35 relatives of adolescents (aged 10 to 19 years old) who died by suicide (Mérelle et al., 2020). There seems to be a lack of knowledge and consensus how to treat this severe chronic suicidal behavior, resulting in stagnation of care and growing demoralization among patients, parents, and mental health care providers. The aim of this paper is to describe characteristics of the suicidal process, to identify challenges experienced in providing mental health care for this subgroup, and to formulate preliminary recommendations. METHOD: A case description from the psychological autopsy study and a review of the relevant literature. RESULTS: The persistent suicidal threat and the resulting despair of the patient and their parents are forcing the mental health care provider into an impasse: the primary focus of treatment slowly moves to guarantee the patient’s safety, which leaves the treatment of underlying problems underexposed. Due to the chronicity of the suicidal ideation and behavior in a phase in which identity formation and developing cognitive and emotional regulation skills are important developmental tasks, we identify a risk of developing a suicidal identity. DISCUSSION: Based on expert knowledge, we make recommendations on 1) treating suicidality as a transdiagnostic phenomenon with its own meaning and function, 2) implementing treatment considerations promoting the autonomy, 3) aiming at continuity of care and prevention of repeated patient referrals by creating a multidisciplinary network of care providers, and 4) making chronic suicidality tolerable for the care provider. CONCLUSION: We propose preliminary practical recommendations in our quest for optimal mental health care for chronically suicidal adolescents.